Studies of Functional Modeling in the IDEF0 Standard as the Initial Stage of TPPs Design - Vasilyevna, Fedorova Natalia; Anatolyevich, Shaforost Dmitry; Radionovna, Bundikova Vera; Anatolyevna, Denisova Irina (Current Approaches in Science and Technology Research Vol. 2, 2021)
A set of regulatory and technical documents regulate the design and operation of thermal power plants (TPPs) in the Russian Federation. It is important to coordinate legal, environmental, and other TPP indicators with specialists of various profiles during the initial design stage, as well as establish a general concept and structure for the station. There are no documents regulating this procedure in the Russian Federation's conventional professional criteria. A methodology and a family of IDEF standards covering all stages and aspects of design were developed and adopted as national standards in a number of countries, including individual products in Russia, at the end of the twentieth and beginning of the twenty-first centuries. The IDEF technique is written in a visual graphical language that can be used for interprofessional communication. The implementation of the IDEF0 specification at the initial design stage of thermal power plants is discussed in this paper. IDEF standards should complement technical standards. These will speed up the design process and increase the efficiency of TPP operation.